Analisis Kinerja Keuangan Berdasarkan Metode economic value added (EVA) Pada PT. Surya Citra Media. Tbk - Eva Susanti; Msy. Mikial; Ima Andriyani; Azmir Ferdinansyah (UNIVED Press, 2022)
This study aims to measure and find out financial performance at PT. Surya Citra Media, Tbk using the method of Economic Value Added (EVA) for the period 2016 - 2020. This study uses this research using descriptive analysis method which aims to provide an overview of the actual financial performance of the company, where data collected, compiled, then analyzed and explained with existing theories and finally make conclusions and suggestions. Descriptive analysis method used in this study to describe in general PT. Surya Citra Media, Tbk, by describing the results of the analysis conducted in this study. The design of this study is to use a qualitative approach, where with this approach the author seeks to understand the analysis of financial performance using EVA methods. The conclusion of this study shows that the financial performance of PT. Surya Citra Media, Tbk based on the analysis of Economic Value Added (EVA) from 2016 to 2020 is not good, where the value of EVA <0, ie for five consecutive years the company EVA shows a negative value. In 2016 the value of EVA - Rp. 788,228,366 and in 2017 the value of EVA again decreased significantly by -Rp. 2,101,912,330 and in 2018 amounting to Rp. 1,237,933,617 and decreased in 2019 to a figure of -Rp. 1,148,156,021 and in 2020 it fell to -Rp. 749,755,182. It is recommended for companies to increase EVA each year to reach a positive value by reducing or reducing the cost of capital while negotiating interest rates.